Pengendalian Misregister pada Cetakan Kemasan Karton di Mesin Offset - Galingging, Rumbel; Sutriono (Magenta | Official Journal STMK Trisakti, 2022)
The offset printing system dominates for the number of prints with medium to small quantities, in the printing process it requires skills and techniques in the printing process from the design process, to the manufacture of offset plates. Many problems that often arise from paper materials and printing techniques, efforts to control the problem of misregister printing on offset sheet-fed machines come from paper that is not angled and from machine factors because the machine is not maintained and because the number of prints is small so the operator ignores the printing process procedure the data is taken from the Pareto analysis tool to the printing process at Indah Sakti Printing on Rawamagun Roast Chicken packaging located in Central Jakarta. From the factors causing problems in the process of printing the â€œPanggang Rawamangunâ€ cardboard packaging on the SM 52 offset sheet-fed machine, the problem is that the gripper pressure is not right so that the print register is difficult to reach and often changes. How to control the prints in the process of printing cardboard packaging by applying the design to be printed in order to minimize the cause of this print misregisters. on the SM 52 offset sheet-fed machine.